Neuropsychiatric Symptoms As The First Manifestation of Juvenile Systemic Lupus Erythematosus: A Complicated Case With Klinefelter's Syndrome - SHIARI*, Reza; HASSASE YEGANE, Mehrnoush; FARIVAR, Shirin; JAVADI PARVANEH, Vadood; MIRJAVADI, Seyed Alireza (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Shiari R, Hassase Yegane M, Farivar S, Javadi Parvaneh V, Mirjavadi SA. Neuropsychiatric symptoms as the first manifestation of Juvenile Systemic Lupus Erythematosus: A complicated case with Klinefelter’s syndrome. Iran J Child Neurol. 2014 Winter; 8(1):62-65. Abstract Systemic Lupus Erythematosus (SLE) is an autoimmune, multisystem disorder with various manifestations. There are limited reports on the neuropsychiatric findings as the first manifestation of SLE in children. Herein, we reported a 14-year-old Iranian boy with a two-year history of cognitive dysfunction and behavioural problems as well as a recent history of epistaxis. The patient workup ended with a diagnosis of Klinefelter’s syndrome associated with juvenile SLE. Patients with Klinefelter’s syndrome may exhibit behavioural problems and psychological disease. These psychiatric disorders could be complicated with lupus in children. In fact, psychiatric symptoms may occur as the first manifestation of juvenile SLE. Specially, if accompanied with Klinefelter’s syndrome. We suggest the diagnosis of SLE must be strongly considered in all children with neuropsychiatric manifestations. References: Brey RL. Neuropsychiatric Lupus, clinical and imaging aspects. Bullet NYU Hosp joint dis 2007;65(3):194-9. Yu CH, Lee MB, Tseng MM, Liao SC. Obsessive-Compulsive symptoms as a manifestation of neuropsychiatric SLE. J Formus Med Assoc 2008;107:68-72. Harel L, Sandborg Ch, Lee T, Scheven E. Neuropsychiatric manifestations in paediatric SLE and association with antiphospholipid antibodies. J Rheumatol 2006;33:1873-7. Bernatsky S, Clarke A, Gladman DD, Urowitz M, Fortin PR, Barr SG, et al. Mortality related to Cerebrovascular disease in SLE. Lupus 2006; 15:835-9. Stern R, Fishman J, Brusman H, Kunkel HG. Systemic lupus erythematosus associated with Klinefelter’s syndrome. Arthritis Rheum 1977; 20:18-22. Paduch DA, Fine RG, Bolyakov AJ. New concepts in Klinefelter syndrome. Curr Opin Urol 2008 Nov;18(6):621-7. Shiari R, Farivar S. juvenile systemic lupus erythematosus associated with Klinefelter’s syndrome; A case report. Rheumatol Clin 2010;6:212-13. Tan EM, Cohen AS, Fries JF, Masi AT, McShane DJ, Rothfield NF, et al. The 1982 revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum 1982;25:1271-7. Karassa FB, Ioannidis JPA, Touloumi G, Boki KA, Moutsopoulos HM. Risk factors for CNS involvement in SLE. Q J Med 2000;93:169-74. West SG. Neuropsychiatric lupus. Rheum Dis Clin North Am 1994;20:129-58. Feinglass EJ, Arnett FC, Dorsch CA, Zizic TM, Stevens MB. Neuropsychiatric manifestation of SLE: Diagnosis, clinical spectrum and relationships to other features of the disease. Medicine (Baltimore) 1976;55:323-39. Robert M, Sunitha R,Thulaseedharan NK. Neuropsychiatric manifestations of SLE: a study from south India. Neurology India 2006;54(1):75-77. Sibbitt WL, Brandit JR, Johnson CR, Maldonado ME, Patel SR, Ford CC, et al. The incidence and prevalence of neuropsychiatric syndromes in paediatric onset SLE. J Rheumatol 2002;29:1536-42. Yu HH, Lee JH, Wang LC,Yang YH, Chiang BL. Neuropsychiatric manifestations in paediatric SLE: a 20-year study. Lupus 2006;15:651-7. Conti F, Alessandri C, Bompane D, Bombardieri M, Spinelli FR, Rusconi. Autoantibody profile in SLE with psychiatric manifestations: a role anti-endothelial-cell antibodies. Arthritis Res Ther 2004;6:366-72. Greenwood DL, Gitlits VM, Alderuccio F, Sentry JW, Toh BH. Autoantibodies in NPSLE. Autoimmunity 2002;35:79-86. Oktenli C, Yesilova A, Kocar IH, et al. Study of autoimmunity in Klinefelter’s syndrome and idiopathic hypogonadotropic hypogonadism. J Clin Immunol 2002; 22:137-143. Brey RL, Holliday SL, Saklad AR, Navarrete MG, Hermosillo-Romo D, Stallworth CL. Neuropsychiatric syndromes in Lupus: prevalence using standardized definitions. Neurology 2002;58:1214-20. McLaurin EY, Holliday SL, Williams P, Brey R. Predictors of cognitive dysfunction in patients with SLE. Neurology 2005;64:297-303. Ampelas JF, Wattiaux MJ, Van Amerongen AP. Psychiatric manifestations of SLE and Sjogren’s syndrome. Encephale 2001;27(6):588-99.